2021
DOI: 10.3389/fgene.2021.747576
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Prognostic Factors of Lipid Metabolism in Obstructive Sleep Apnea

Abstract: Background: Obstructive sleep apnea (OSA) is considered to be an independent factor affecting lipid metabolism. This study explored the relationship between immune genes and lipid metabolism in OSA.Methods: Immune-related Differentially Expressed Genes (DEGs) were identified by analyzing microarray data sets from the Gene Expression Omnibus (GEO) database. Subsequently, we conducted protein-protein interaction (PPI) network analysis and calculated their Gene Ontology (GO) semantic similarity. The GO, Kyoto Enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Our data demonstrated the immune cell changes of VAT in the OSA group. Consistent with previous findings (Peng et al, 2021), monocyte-macrophages accounted for the highest proportion of immune cell types, followed by CD8 T cells. The changes in M1 and M2 macrophage proportion showed a significant difference between OSA and the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data demonstrated the immune cell changes of VAT in the OSA group. Consistent with previous findings (Peng et al, 2021), monocyte-macrophages accounted for the highest proportion of immune cell types, followed by CD8 T cells. The changes in M1 and M2 macrophage proportion showed a significant difference between OSA and the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, the results of the bioinformatic analysis are not always reliable, especially in small sample datasets, experimental validation is necessary to increase confidence. In addition, we did not further establish an immune-related diagnostic model for OSA when compared to previous studies (Li et al, 2017;Gu et al, 2019;Cao et al, 2021;Peng et al, 2021;Liu et al, 2022), because of the invasive procedures for harvesting VAT.…”
Section: Discussionmentioning
confidence: 88%
“…All the above reports confirmed OSA/IH induces the disorder of adipocytes (the body’s metabolic regulatory organ). Several studies have focused on the effects of OSA on dyslipidemia and lipid metabolism ( Barros and García-Río,2019 ; Peng et al, 2021 ). These data suggest that IH induces hyperlipidemia, and results in the up-regulation of genes involved in lipid biosynthesis in the liver and adipose tissue, and increased lipoprotein secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Yuanyuan Cao et al [ 8 ] screened and identified potential biomarkers of OSA and its related diseases by microarray analysis. Peng Lu et al [ 9 ] established and validated the prognostic model of OSA based on microarray datasets and relevant bioinformatics analysis, providing a basis for further research on the molecular mechanism and potential targets of lipid metabolism regulation of OSA. However, few studies have involved gene markers related to different severity of OSA.…”
Section: Introductionmentioning
confidence: 99%